1961
DOI: 10.1001/jama.1961.63040200015016a
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Adenocarcinoma of the Jejunum and Nontropical Sprue

Abstract: CommentThe reported case is unusual, first, because a desmoid tumor was found in the abdominal wall inside of the costal arch. Gatchell, Clagett, and McDonald8 recently reported a case in which a desmoid tumor arose from the intercostal muscles of the right upper thorax. The second unusual feature is that the desmoid tumor involved the adherent colon. Considering the patient's history of prolonged abdominal distress following an automobile accident 10 years prior to the present admission, it seems plausible th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1965
1965
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Finally, numerous studies have confirmed the association between CD and B-cell lymphoma284286 and CD and small intestinal adenocarcinoma 42 254 287289…”
Section: Gluten-free Dietmentioning
confidence: 90%
“…Finally, numerous studies have confirmed the association between CD and B-cell lymphoma284286 and CD and small intestinal adenocarcinoma 42 254 287289…”
Section: Gluten-free Dietmentioning
confidence: 90%
“…Girdwood et al (1961) described the coexistence of subtotal villous atrophy in a jejunal biopsy, malabsorption, and an anaplastic carcinoma 70 cm. below the duodeno-jejunal junction; and Moertel and Hargraves (1961) have also reported a case in which jejunal adenocarcinoma complicated long-standing malabsorption, and was associated with villous atrophy of the jejunal mucosa. It may well be that case 18 in my series represents a fifth example of jejunal adenocarcinoma complicating idiopathic steatorrhoea in a clinicallyasymptomatic phase;the mucosal abnormalities in this case certainly form a striking contrast to the relatively normal mucosa observed in the other cases of small-bowel carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…One of these was a woman of 56 years who developed an adenocarcinoma of the stomach. The other report was by Moertel and Hargraves (1961) who describe a man of 68 years who had non-tropical sprue for 11 years and developed an adenocarcinoma of the jejunum. Ogilvie and Shaw (1955), in an article on 'primary tumours of the small bowel', included a man of 40 years, who had had 'steatorrhoea for years' and developed an adenocarcinoma of the duodenojejunal junction.…”
Section: Discussionmentioning
confidence: 99%